Masculine generic pronouns as a gender cue in generic statements. Issue 10 (26th November 2022) - Redl, Theresa; Szuba, Agnieszka; de Swart, Peter; Frank, Stefan L.; de Hoop, Helen
ABSTRACT: An eye-tracking experiment was conducted with speakers of Dutch ( N = 84, 36 male), a language that falls between grammatical and natural-gender languages. We tested whether a masculine generic pronoun causes a male bias when used in generic statements—that is, in the absence of a specific referent. We tested two types of generic statements by varying conceptual number, hypothesizing that the pronoun zijn "his" was more likely to cause a male bias with a conceptually singular than a conceptually plural antecedent (e.g., Someone (conceptually singular)/ Everyone (conceptually plural) with perfect pitch can tune his instrument quickly ). We found male participants to exhibit a male bias but with the conceptually singular antecedent only. Female participants showed no signs of a male bias. The results show that the generically intended masculine pronoun zijn "his" leads to a male bias in conceptually singular generic contexts but that this further depends on participant gender.